The Right to Make Mistakes? The Limits to Adaptive Planning for Climate Change - Andrew Kirby (Challenges, 2022)
While the UN recognizes the right of individuals “to take risks and make mistakes”, there are reasons to question whether this right can be universal. In the context of a changing climate, it is imperative that individuals have access to a safe and sustainable environment; yet we must ask if this covenant is broken if people choose to place themselves in harm’s way. In its first part, this paper explores outcomes of climate change denial, manifested as continued migration to dangerous locations, and skepticism for adaptive strategies. The second half of the paper explores how localities can create a false narrative concerning risks, and asks whether communities also have a right to make mistakes?